1996
DOI: 10.1104/pp.112.3.1321
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Acid Invertase (TIV1) Gene Alters Soluble Sugar Composition and Size in Transgenic Tomato Fruit

Abstract: Invertases (P-fructosidase, EC 3.2.1.26) are a group of related enzymes that hydrolyze Suc to Glc and Fru. Acid invertase has a pH optimum for activity between 3 and 5, whereas neutra1 invertase has a pH optimum of about 7. Acid invertases are divided into vacuolar (or soluble) and extracellular (or insoluble) forms, with acid (Unger et al., 1992) and basic (Laurière et al., 1988) pls, respectively. Neutra1 (or alkaline) invertase is presumed to be localized in the cytosol (Ricardo, 1974). Plant genes for acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
141
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(158 citation statements)
references
References 25 publications
14
141
0
3
Order By: Relevance
“…Instead, organic acids and potassium ions rather than sugars are the dominant contributors to the osmotic potential of potato tubers (Bethke et al, 2009). This situation is distinctly different from that in developing tomato fruit, where invertase activity and hexose accumulation function in the hydrolysis of Suc and turgor-driven fruit growth, respectively (Klann et al, 1996). In carrot taproots and in developing muskmelon fruit, vacuolar acid invertase activity is thought to have a similar role in promoting growth by producing hexoses that decrease osmotic potentials and promote water uptake (Tang et al, 1999;Yu et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Instead, organic acids and potassium ions rather than sugars are the dominant contributors to the osmotic potential of potato tubers (Bethke et al, 2009). This situation is distinctly different from that in developing tomato fruit, where invertase activity and hexose accumulation function in the hydrolysis of Suc and turgor-driven fruit growth, respectively (Klann et al, 1996). In carrot taproots and in developing muskmelon fruit, vacuolar acid invertase activity is thought to have a similar role in promoting growth by producing hexoses that decrease osmotic potentials and promote water uptake (Tang et al, 1999;Yu et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…In tomato (Solanum lycopersicum), antisense silencing of the acid invertase gene resulted in a 30% reduction in fruit size (Klann et al, 1996). In carrot (Daucus carota) and muskmelon (Cucumis melo), silencing of the acid invertase gene significantly altered plant and root/fruit development (Tang et al, 1999;Yu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse genetic approaches have demonstrated that alterations in fruit metabolism/composition may affect fruit development and vice-versa. As an example, increasing fruit Suc content by down-regulating invertase or vacuolar ATPase genes affects fruit growth and fruit size (Klann et al, 1996;Amemiya et al, 2006). Conversely, altering the ethylene-dependent signal transduction networks has a considerable effect on fruit ripening and associated changes, including fruit color, aroma, sugar, and organic acids (Wilkinson et al, 1995;Barry and Giovannoni, 2006;Carrari and Fernie, 2006;Giovannoni, 2007).…”
mentioning
confidence: 99%
“…There is believed to be a trade-off between fruit sugar content and yield. For example, while the sugar content of tomato fruit increases as a result of the increased ratio of sucrose to hexose through the suppression of vacuolar invertase gene expression, the fruit size decreases (Klann et al, 1996); fruit size and yield generally decrease as fruit sugar content increases in tomato plants grown under salinity stress conditions (Saito et al, 2008;Sarkar et al, 2008). However, fruit size and yield do not appear to decrease in IL8-3 and SIRT-engineered tomato plants, which contain a higher fruit sugar content, as described above; and in other ILs, the fruit yield does not always decrease even if their fruits exhibit high sugar contents (Baxter et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%